The Effect Of Urbanizaation, Industrialization, And Economic Growth On Renewable Energy Consumption In Asean-6 Period 1994-2020 - Shafira Annisa; Dessy Rachmawatie; Dimas Bagus Wiranata Kusuma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the influence of urbanization, industrialization, and economic growth on renewable energy consumption in ASEAN-6 (1994 - 2020). The data used in this research is annual data for period 1994 – 2020 taken from the World Bank Data. The estimation tool used in this research is the Vector Error Correction Model (VECM) using EViews 12. The research results show that in the short term, urbanization, industrialization, and economic growth reveal insignificant effect on renewable energy consumption in ASEAN-6. Meanwhile in the long term, variables show varying results. Urbanization and Economic Growth have a negative and significant effect with coefficient numbers -0.138775 and -0.364414, while Industrialization has a positive and significant effect with a coefficient of 0.423784. These findings indicate that ASEAN-6 must prioritize deploying renewable energy sources to meet its mix energy target. Therefore, the reliance on non-renewable energy can shift and create sustainable energy development and anticipate energy security issue.